Film layer structure of window layer of thin-film solar cell and preparation method of film layer structure
By adopting a three-layer film structure, including a low-doped aluminum zinc oxide film layer, an upper tin oxide film layer and a transparent indium tin oxide conductive film layer, the problem of poor density and intimate bonding of the thin-film solar cell window layer is solved, and the performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411738955.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-28
AI Technical Summary
The existing thin-film solar cell window layer has poor density and is not tightly bonded between the film layers, resulting in further improvement in battery device performance.
A three-layer film structure is adopted, wherein the first window film layer is a low-doped aluminum zinc oxide film layer, the second window film layer is an upper tin oxide film layer prepared by atomic layer deposition, and the third window film layer is a transparent indium tin oxide conductive film layer, which is prepared by magnetron sputtering and atomic layer deposition, so as to improve the density and binding force of the film layer.
The open circuit voltage, filling factor and conversion efficiency of thin-film solar cells are improved, and the performance of the battery is enhanced, especially the problem of holes in the zinc oxide film layer with low doped aluminum has been improved.
Smart Images

Figure CN119730477A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thin-film solar cells, and in particular to a film layer structure of a window layer of a thin-film solar cell and a preparation method thereof. Background Art
[0002] Existing thin-film solar cells, such as the third-generation copper indium gallium selenide thin-film solar cells (CIGS), have a film structure including a stainless steel substrate, a barrier layer, a metal back electrode, a light absorption layer, a buffer layer, a window layer, and a metal gate electrode. The thickness of each functional film layer is between tens and thousands of nanometers, and is used to carry different functions. For the window layer (TCO), common ones include intrinsic zinc oxide film layers or low-aluminum-doped zinc oxide film layers (i-ZnO), and heavily-aluminum-doped zinc oxide film layers (AZO) on i-ZnO film layers, or transparent conductive oxide film layers (ITO) on i-ZnO film layers. Among them, the i-ZnO film layer, AZ The i-ZnO film layer and the ITO film layer are prepared in sequence by magnetron sputtering (PVD). However, the window layer prepared by PVD consisting of the i-ZnO film layer and the AZO film layer currently has the problems of poor film density and loose bonding between the film layers, which will lead to low open circuit voltage and filling factor of the thin film battery, and then lead to low battery conversion efficiency. Even if the AZO film layer is replaced by the ITO film layer, thanks to the high conductivity and low resistivity of ITO, the battery device performance can be improved to a certain extent, but the improvement is limited. Therefore, the existing thin-film solar cells urgently need to break through the limitations of the traditional window layer film structure to further improve the device performance of the battery. Summary of the invention
[0003] In view of this, the purpose of the present invention is to propose a film layer structure of a thin-film solar cell window layer and a preparation method thereof, so as to solve the problem that the film layer density of the existing traditional window layer film layer structure is poor and the bonding between the film layers is not tight, which leads to the problem that the performance of the battery device needs to be further improved.
[0004] Based on the above purpose, the present invention provides a film layer structure of a thin-film solar cell window layer, which is arranged between a buffer layer and an electrode layer of a thin-film solar cell, comprising:
[0005] A first window film layer is disposed on the buffer layer, a second window film layer is disposed on the first window film layer, and a third window film layer is disposed on the second window film layer, wherein the third window film layer is a transparent indium tin oxide conductive film layer;
[0006] The second window film layer is an upper tin oxide film layer, and the upper tin oxide film layer is prepared by atomic layer deposition;
[0007] The first window film layer is a transparent conductive oxide film.
[0008] Preferably, the first window film layer is a low-aluminum-doped zinc oxide film layer with a thickness of 50 nm to 120 nm, and is prepared by magnetron sputtering.
[0009] Preferably, the first window film layer is a lower tin oxide film layer with a thickness between 10 nm and 20 nm, and is prepared by spin coating.
[0010] The present invention also provides a method for preparing a window layer of a thin-film solar cell, comprising the following steps:
[0011] A short film on which a barrier layer, a metal back electrode, a light absorption layer, a buffer layer, and a first window film layer have been plated on a stainless steel substrate is selected as a bottom cell, and the short film is cut into small cell samples;
[0012] Select the cut battery sample and prepare the second window film layer by atomic layer deposition;
[0013] A battery sample with a second window film layer prepared was selected, and a transparent indium tin oxide conductive film layer was prepared by magnetron sputtering;
[0014] Select a battery sample with the third window film layer prepared, and then perform electrode evaporation;
[0015] Conduct battery performance test on battery samples with electrode vapor deposition.
[0016] Alternatively, a short film on which a barrier layer, a metal back electrode, a light absorbing layer and a buffer layer have been plated on a stainless steel substrate is selected as a bottom cell, and the short film is cut into small cell samples;
[0017] Select the cut battery sample and prepare the first window film layer by spin coating;
[0018] Select a battery sample with the first window film layer prepared, and use atomic layer deposition to prepare the second window film layer;
[0019] A battery sample with a second window film layer prepared was selected, and a transparent indium tin oxide conductive film layer was prepared by magnetron sputtering;
[0020] Select a battery sample with the third window film layer prepared, and then perform electrode evaporation;
[0021] Conduct battery performance test on battery samples with electrode vapor deposition.
[0022] Preferably, in the preparation of the first window film layer, a cut battery sample is first selected and fixed with a clamp to be purged of dust;
[0023] Heating table, heating temperature is between 150℃ and 200℃;
[0024] Take the purged battery sample and place it on the workbench, take 100ul to 200ul of tin oxide solution and drop it on the battery sample;
[0025] Control the workbench to rotate at a speed between 3000 rpm and 4000 rpm, and the rotation time between 30 seconds and 50 seconds;
[0026] Take the spin-coated battery sample and place it on the annealing table for annealing.
[0027] The beneficial effects of the present invention are as follows: compared with the existing traditional thin-film solar cell window layer, which only includes a low-doped aluminum zinc oxide film layer and a third window film layer, a total of two layers, wherein the third window film layer can be a transparent indium tin oxide conductive film layer or a heavily doped aluminum zinc oxide film layer, and both are prepared by magnetron sputtering, there are problems of poor film density and loose bonding between film layers, especially there are many holes on the low-doped aluminum zinc oxide film layer, which is relatively uneven, by changing the existing window layer to a first window film layer, a second window film layer and a third window film layer deposited in sequence, a total of three layers, wherein the first window The film layer still uses a low-aluminum-doped zinc oxide film layer, which is thinned, and an upper tin oxide film layer prepared by atomic layer deposition is inserted between the conventional first window film layer and the third window film layer, or the low-aluminum-doped zinc oxide film layer prepared by traditional magnetron sputtering is directly replaced with a double-layer tin oxide layer, including a lower tin oxide film layer prepared by spin coating and an upper tin oxide film layer prepared by atomic layer deposition, and is matched with a transparent indium tin oxide conductive film layer to construct a new film layer structure for the window layer of a thin-film solar cell, which solves the problems of poor film density and loose bonding between film layers. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 It is a schematic diagram of the structure of the window layer of an existing traditional thin-film solar cell;
[0030] Figure 2 This is a schematic diagram of the structure of inserting a single layer of tin oxide to construct a window layer of the present invention;
[0031] Figure 3 This is a schematic diagram of the structure of the window layer constructed by using a double layer of tin oxide in the present invention;
[0032] Figure 4 It is a structural schematic diagram of the liquid taking gun of the present invention during the liquid taking process;
[0033] Figure 5 It is a schematic diagram of the structure of spin coating on the workbench of the present invention;
[0034] Figure 6 It is a schematic diagram of the structure during annealing on the annealing table of the present invention.
[0035] The markings in the figure are:
[0036] 1. Stainless steel substrate; 2. Barrier layer; 3. Metal back electrode; 4. Light absorption layer; 5. Buffer layer; 60. Zinc oxide film layer; 61. Lower tin oxide film layer; 62. Upper tin oxide film layer; 63. Transparent indium tin oxide conductive film layer; 7. Electrode layer; 8. Battery sample; 9. Workbench; 10. Annealing table; 11. Liquid gun; 12. Solution cup;. DETAILED DESCRIPTION
[0037] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0038] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should be understood by people with ordinary skills in the field to which the present invention belongs. The "first", "second" and similar words used in the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. "Include" or "comprise" and similar words mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. "Connect" or "connected" and similar words are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.
[0039] like Figure 2 , Figure 3 As shown, a film layer structure of a thin-film solar cell window layer is arranged between a buffer layer 5 and an electrode layer 7 of the thin-film solar cell, including a first window film layer arranged on the buffer layer 5, a second window film layer arranged on the first window film layer, and a third window film layer arranged on the second window film layer, the third window film layer is a transparent indium tin oxide conductive film layer 63, the second window film layer is an upper tin oxide film layer 62, the upper tin oxide film layer 62 is prepared by atomic layer deposition, and the first window film layer is a transparent conductive oxide thin film.
[0040] As an optional embodiment of the present invention, Figure 2As shown, the first window film layer is a low-doped aluminum zinc oxide film layer 60, and is prepared by magnetron sputtering. The conventional window layer is Figure 1 As shown, it only includes a low-doped aluminum zinc oxide film layer 60 and a third window film layer, a total of two layers, wherein the third window film layer can be a transparent indium tin oxide conductive film layer 63, or a heavily doped aluminum zinc oxide (AZO), but the traditional window layer is prepared by magnetron sputtering (PVD), and there are problems such as poor film density and loose bonding between film layers, especially there are many holes on the low-doped aluminum zinc oxide film layer 60, which is relatively uneven, and by changing the existing window layer to a first window film layer, a second window film layer and a third window film layer deposited in sequence, a total of three layers, wherein, as shown Figure 2 As shown, the first window film layer still uses a low-aluminum-doped zinc oxide film layer 60, but the thickness is between 50nm and 120nm, which is about 60% thinner than the traditional low-aluminum-doped zinc oxide film thickness between 250nm and 350nm. In addition, an upper tin oxide film layer 62 is inserted between the conventional first window film layer and the third window film layer, that is, a tin oxide layer prepared by atomic layer deposition, which helps to fill the holes on the low-aluminum-doped zinc oxide film layer 60 and improve the density of the film surface, making the film surface smoother. On the other hand, tin oxide has a better carrier transport capability than low-aluminum-doped zinc oxide, so tin oxide is preferably used for atomic deposition.
[0041] The method for preparing the above-mentioned thin-film solar cell window layer comprises the following steps:
[0042] A short film on which a barrier layer 2, a metal back electrode 3, a light absorption layer 4, a buffer layer 5 and a first window film layer have been plated on a stainless steel substrate 1 is selected as a bottom cell, and the short film is cut into cell samples 8;
[0043] Select the cut battery sample 8 and prepare the second window film layer by atomic layer deposition;
[0044] A battery sample 8 with a second window film layer prepared is selected, and a transparent indium tin oxide conductive film layer 63 is prepared by magnetron sputtering;
[0045] Select the battery sample 8 with the third window film layer prepared, and then perform electrode evaporation;
[0046] The battery performance test was carried out on the battery sample 8 after the electrode was evaporated.
[0047] The following is a comparison of the electrical performance differences between ITO / AZO and i-ZnO without inserting the upper tin oxide film layer 62 and inserting the upper tin oxide film layer 62:
[0048] Group Isc(A) Voc(V) FF(%) Eff(%) Jsc(mA / cm2) A(do SnO2) 0.030-0.34 0.69-0.71 79-84 18.5-19.5 32.25-33.60 B(No SnO2) 0.030-0.34 0.65-0.67 75-79 16.5-17.5 32.10-32.50
[0049] According to the test data, the open circuit voltage Voc (V) of SnO2 is increased by 20mV-60mV, the fill factor FF (%) is increased by 4-5 points, the conversion efficiency Eff (%) is increased by 1-3 points, and the current density Jsc (mA / cm2) is slightly improved compared to the case without SnO2.
[0050] As an optional embodiment of the present invention, Figure 3 As shown, the first window film layer is a lower tin oxide film layer 61, and is prepared by spin coating. Therefore, in the window layer, the low-aluminum-doped zinc oxide film layer 60 prepared by traditional magnetron sputtering is replaced by a double-layer tin oxide layer, including a lower tin oxide film layer 61 prepared by spin coating and an upper tin oxide film layer 62 prepared by atomic layer deposition, and matched with an (ITO) transparent indium tin oxide conductive film layer 63, to construct a new film layer structure of the window layer of a thin-film solar cell, wherein the thickness of the tin oxide film prepared by spin coating is only between 10nm and 20nm, and the thickness of the upper tin oxide film layer 62 prepared by atomic layer deposition is much lower than that of the traditional window layer. Spin coating of tin oxide will form pinholes and defects during the film formation process, resulting in current leakage. Atomic deposition can add another layer to reduce holes and protect the tin oxide film. In addition, it can achieve gradient energy levels, enhance carrier transmission and reduce hysteresis, increase wettability and light transmittance, etc. However, the atomic deposition process of low-aluminum-doped zinc oxide is difficult and the film quality is uncertain, so tin oxide deposition is used to achieve better results.
[0051] The method for preparing the above-mentioned thin-film solar cell window layer comprises the following steps:
[0052] A short film on which a barrier layer 2, a metal back electrode 3, a light absorption layer 4, and a buffer layer 5 have been plated on a stainless steel substrate 1 is selected as a bottom cell, and the short film is cut into cell samples 8;
[0053] Select the cut battery sample 8 and prepare the first window film layer by spin coating;
[0054] Select the battery sample 8 with the first window film layer prepared, and prepare the second window film layer by atomic layer deposition;
[0055] A battery sample 8 with a second window film layer prepared is selected, and a transparent indium tin oxide conductive film layer 63 is prepared by magnetron sputtering;
[0056] Select the battery sample 8 with the third window film layer prepared, and then perform electrode evaporation;
[0057] The battery performance test was carried out on the battery sample 8 after the electrode was evaporated.
[0058] In the preparation of the first window film layer, the cut battery sample 8 is first selected and fixed with a clamp to be purged of dust;
[0059] A heating table 9, the heating temperature is between 150°C and 200°C;
[0060] like Figure 5 As shown, take the purged battery sample 8 and place it on the workbench 9, and drop 100ul to 200ul of tin oxide solution on the battery sample 8;
[0061] The workbench 9 is controlled to rotate at a speed between 3000 rpm and 4000 rpm, and the rotation time is between 30 seconds and 50 seconds;
[0062] like Figure 6 As shown, the spin-coated battery sample 8 is taken and placed on an annealing station 10 for annealing.
[0063] Specifically, Figure 4 As shown, the liquid is taken through a liquid taking gun 11 with a measuring range of 200ul, the liquid taking volume is set to 100 to 200ul, and the liquid is taken from the solution cup 12.
[0064] The following is a comparison of the electrical properties of double-layer tin oxide window films and traditional window films:
[0065]
[0066] According to the test data, the double-layer tin oxide has an open circuit voltage Voc (V) that is 20mV-30mV higher than the traditional window film layer, a fill factor FF (%) that is 3-4 points higher, a conversion efficiency Eff (%) that is 1-3 points higher, and the most obvious improvement in current density Jsc (mA / cm2), which is about 4 to 7 points higher. While the efficiency is improved, the thickness of the newly built window layer is about 60% less than that of the traditional window layer, which greatly reduces the use of target materials during the film deposition process.
[0067] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A film layer structure of a thin-film solar cell window layer, arranged between a buffer layer and an electrode layer of a thin-film solar cell, characterized in that: include: a first window film layer disposed on the buffer layer, a second window film layer disposed on the first window film layer, and a third window film layer disposed on the second window film layer, wherein the third window film layer is a transparent indium tin oxide conductive film layer; The second window film layer is an upper tin oxide film layer, and the upper tin oxide film layer is prepared by atomic layer deposition; The first window film layer is a transparent conductive oxide film.
2. The film layer structure of the thin-film solar cell window layer according to claim 1, characterized in that: The first window film layer is a low-aluminum-doped zinc oxide film layer with a thickness of 50nm to 120nm, and is prepared by magnetron sputtering.
3. The film layer structure of the thin-film solar cell window layer according to claim 1, characterized in that: The first window film layer is a lower tin oxide film layer with a thickness between 10nm and 20nm, and is prepared by spin coating.
4. The method for preparing the film structure of the window layer of a thin-film solar cell according to claim 2, characterized in that: The following steps are involved: A short film on which a barrier layer, a metal back electrode, a light absorption layer, a buffer layer, and a first window film layer have been plated on a stainless steel substrate is selected as a bottom cell, and the short film is cut into small cell samples; Select the cut battery sample and prepare the second window film layer by atomic layer deposition; A battery sample with a second window film layer prepared was selected, and a transparent indium tin oxide conductive film layer was prepared by magnetron sputtering; Select a battery sample with the third window film layer prepared, and then perform electrode evaporation; Conduct battery performance test on battery samples with evaporated electrodes.
5. The method for preparing the film structure of the window layer of a thin-film solar cell according to claim 3, characterized in that: The following steps are involved: A short film on which a barrier layer, a metal back electrode, a light absorption layer and a buffer layer have been plated on a stainless steel substrate is selected as a bottom cell, and the short film is cut into small cell samples; Select the cut battery sample and prepare the first window film layer by spin coating; Select a battery sample with the first window film layer prepared, and use atomic layer deposition to prepare the second window film layer; A battery sample with a second window film layer prepared was selected, and a transparent indium tin oxide conductive film layer was prepared by magnetron sputtering; Select a battery sample with the third window film layer prepared, and then perform electrode evaporation; Conduct battery performance test on battery samples with evaporated electrodes.
6. The method for preparing a film structure of a thin-film solar cell window layer according to claim 5, characterized in that: In the preparation of the first window film layer, the cut battery sample is first selected and fixed with a clamp to be blown away by dust; Heating table, heating temperature is between 150℃ and 200℃; Take the purged battery sample and place it on the workbench, take 100ul to 200ul of tin oxide solution and drop it on the battery sample; Control the workbench to rotate at a speed between 3000 rpm and 4000 rpm, and the rotation time between 30 seconds and 50 seconds; Take the spin-coated battery sample and place it on the annealing table for annealing.